Molecular uncovering of important helminth species in wild ruminants in the Czech Republic - Škorpíková, Lucie; Vadlejch, Jaroslav; Ilgová, Jana; Plhal, Radim; Drimaj, Jakub; Mikulka, Ondřej; Magdálek, Jan; Kašný, Martin; Reslová, Nikol (Frontiers in Veterinary Science, 2025)
Monitoring gastrointestinal helminth infections in wild ruminants poses significant challenges for managing wildlife health, particularly regarding invasive species. Traditional coprological methods are often limited by their labor-intensive nature and potential for erroneous identification due to morphological similarities among parasite species. This study employed advanced molecular techniques to assess the prevalence and distribution of several helminth taxa, including the invasive nematode Ashworthius sidemi and the trematode Fascioloides magna, in wild ruminant populations in the Czech Republic (CR). A comprehensive and extensive survey on parasite occurrence, unique in its nationwide scope, was conducted on 983 fecal samples collected from red deer (Cervus elaphus), roe deer (Capreolus capreolus), fallow deer (Dama dama), and mouflon (Ovis musimon) across various regions of the CR. The samples were analyzed using multiplex real-time PCR assays specifically designed to detect the DNA of six helminth representatives: the nematodes A. sidemi and Haemonchus spp., as well as the trematodes F. magna, Dicrocoelium dendriticum, Fasciola hepatica, and Calicophoron daubneyi (and representatives of the family Paramphistomidae, respectively). These assays targeted regions of ribosomal DNA (rDNA) and were designed to exhibit high sensitivity and specificity, enabling accurate detection of helminth parasites directly in fecal samples. The molecular assays revealed that invasive nematode A. sidemi was the most prevalent helminth species, detected in 15.8% of all samples (155/983), with the highest infection rate observed in red deer at 30.7% (124/404). Haemonchus spp. were also frequently detected, identified in 14.9% of samples (146/983), particularly in roe deer, with a prevalence of 23.2% (86/371). Spatial analysis of these nematodes across various regions of the CR revealed the extensive distribution of both A. sidemi and Haemonchus spp. in nearly all regions. In contrast, trematode infections were less common, with F. magna and D. dendriticum each found in only 1.5% of samples (15/983). Members of the family Paramphistomidae were detected in 0.2% of the samples (2/983) and were confirmed through sequencing as C. daubneyi. The geographical distribution patterns identified in this study indicate potential hotspots for specific helminth species. These findings are critical for planning health management and conservation strategies to mitigate the impacts of helminth infections, especially in areas affected by invasive species.